SYNTHESIS OF MERCAPTO ETHYLESTER FROM PALM FATTY ACID: WATER DEHYDRATION AS BYPRODUCT WITH AZEOTROPIC DISTILLATION - Patuan Anggi Sitompul, Andri
Polyvinyl chloride (PVC) is a polymer which is commonly used in daily life, such as material for construction, pipe production, and cable insulation. PVC has advantages, such as its good stability to chemical substance, good electrical insulators, and low production cost. With these benefits and advantages, PVC has good prospect in this present time and future. However, PVC has a weakness if exposed to high temperatures (from 80°C), PVC will experience thermal degradation. To overcome this weakness, it is essential to add thermal stabilizer additive. Indonesia is the biggest palm producer country in the world, as well as the world’s second biggest tin. By utilizing this potential, it is necessary to develop a lead-based PVC thermal stabilizer with source of fatty acid from palm oil. Such type stabilizer can be synthesized from mercaptoethyl ester of fatty acid (MEFA) and methyl tin chloride (MTC). MEFA can be produced by an equilibrium reaction between palm fatty acid distillate (PFAD) with mercaptoethanol (ME). This reseach is aimed to study the synthesis of MEFA using PFAD. The synthesis was carried out in a two-necked flask connected to condenser and barrett trap. Water as a byproduct was removed by using azeotropic distillation in ambient pressure by utilising cyclohexane as entrainer and p-toluene sulfonic acid as catalyst. Entrainer to fatty acid ratio was varied within ranges of 0,5 – 3. The fatty acid and entrainer were also varied to analyze the product quality. Oleic acid was used to study the effect of ME excess in the ranges of 10 – 100%-mole. Product quality was evaluated by measuring the mercaptant content and yield of MEFA. The mercaptant content and yield of MEFA were in the ranges of 5,8 – 7,7% and 57-77%, respectively. A 22 factorial design showed that mercaptant content and yield increased along with the increasing of entrainer to fatty acid ratio and ME excess. The dehydration of water using azeotropic distillation had given a shorter reaction time compared with vacuum distillation, but resulted in a lower product quality.